AYAH DAN KEADILAN GENDER: MEMBACA ULANG PERAN AYAH-IBU DALAM KELUARGA INDONESIA PERSPEKTIF AMINA WADUD - Fatimah Tuzaroh; Adhimas Alifian Yuwono; Ahmad Fauzi (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Fatherless is a condition of psychological absence of fathers in the growth and development of children in household life. This research aims to analyze the phenomenon of fatherlessness in Indonesia due to patriarchal culture, using Amina Wadud's feminist thinking about the concept of caring for children. This research uses a qualitative method with a literature study approach, namely by collecting books, journals, and websites related to the research theme. The analysis used is critical analysis by describing the formal object, namely Amina Wadud's thinking, to be used as an analysis of the material object, namely the fatherless phenomenon in Indonesia. The results of the analysis of this study are fatherless conditions due to patriarchal culture should not occur because; first, the Qur'an states that the rights and obligations in caring for children between men and women are the same. Second, a flexible system of cooperation is key in the household, including in terms of caring for children. Third, women also have the right to be as productive as men, not just focusing on childcare.